KEEFEKTIFAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS III SDN 1 PAKALU I - Endah Lestari, Putri; Rahman Rahim, Abdul; Bahri, Aliem (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem of this research is to determine the effectiveness of differentiated learning on Indonesian language learning outcomes for third-grade students at SDN 1 Pakalu I. This study aims to investigate the effectiveness of differentiated learning on Indonesian language learning outcomes for third-grade students at SDN 1 Pakalu I in classes that use differentiated learning and those that do not, as well as to determine whether there are differences in Indonesian language learning outcomes among third-grade students at SDN 1 Pakalu I. This study uses a quasi-experimental research method. The population of this study consists of all third-grade students at SDN 1 Pakalu I. The sampling technique used is total sampling or saturated sampling. The instrument used is a test instrument in the form of multiple-choice questions to measure student learning outcomes with a Pre-Test Post-Test Control Group Design. Based on the research findings, the Indonesian language learning outcomes of students in the experimental class that used differentiated learning showed 94% in the category of mastery learning and 6% in the category of not mastering. The level of Indonesian language learning outcomes in the control class that did not use differentiated learning showed 50% mastery learning and 50% not mastering. The hypothesis test results obtained a sig (2-tailed) of 0.000, meaning H0 is rejected (0.000 < 0.05). H1 is accepted because sig (tailed) > α or (0.166 > 0.05). In the T-test analysis, sig > t-table or (4.742 > 2.036). The hypothesis testing concludes that there is a significant difference in learning outcomes between students in the experimental class using the differentiated learning approach and the control class using conventional learning models in Indonesian language learning at SDN 1 Pakalu I.